Digital savviness: does it matter for open and distance learning? / Alice Shanthi Kasawi@Krisnan ... [et al.] - Kasawi@Krisnan, Alice Shanthi; Jamil, Nur Izzah; Ahmad, Siti Noor Dina; Lim, Teck Heng (Universiti Teknologi MARA Cawangan Kedah, 2022)
The Open and Distance Learning (ODL) approach was adopted in Malaysia for teaching and learning when the COVID-19 pandemic hit the world. The speed at which students shifted from physical lessons to online classes created problems for some, particularly those who were not computer savvy. The ACE website was formed to help those less computer savvy adapts to online learning. ACE is a compilation of freely available tools and applications and step-by-step guidance for using the tools and apps to create attractive and interactive presentations. A study was carried out to explore university students' perceptions of ACE and how helpful the website's content was in assisting them in completing their English course assignments. Non-probability and quota sampling techniques were used to collect pre-and post-responses to ACE using an online questionnaire. The overall sample size was 186 participants who filled out pre-and post-surveys. The data set covers students' perceptions of utilising ACE's various tools and applications to complete their English course assignments. The results show that most respondents claimed that ACE had helped them prepare more attractive and engaging presentations that included embedded video and audio. When recording student presentations, students still prefer to use their cell phone cameras when it is an individual presentation. However, the results show a shift in using ZOOM to record group presentations after adopting ACE. This study comes to the conclusion that the ACE website has helped students make better presentations so that they can teach and learn English more effectively during ODL.